GAMBARAN PERILAKU MAHASISWA SERUMPUN FAKULTAS KESEHATAN UNIVERSITAS SUMATERA UTARA TERHADAP PROSES PENCARIAN PENGOBATAN DI KOTA MEDAN TAHUN 2013 - Nurmaines Adhyka; Alam Bakti; namora lumongga (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Treatment search process is a process performed by a person in response to pathological reactions that occur within his body. The search process is made up of medical knowledge and attitude towards his condition. Knowledge and attitudes can be formed of a good education. Clumps student health faculty learn it so, it would be good to see how the image of student behavior in the process searching of  medical treatment. This type of research is a descriptive study with a survey method. The population in this study were all students of the Faculty of Medicine (FK), School of Public Health (FKM) and School of Nursing (FKep) University of North Sumatra regular program who active force from 2009 to 2012 with a sample size of 93 student. The samples came from 44 medical students, 35 public health students and 14 students of Nursing Faculty. Presentation of data using frequency distribution tables. The results showed that the characteristics of the respondents had been studying for 2 and 4 semesters as many as 28 students (30.1%), female sex as many as 59 students (63.4%), with the 19-20 year age group as many as 48 students (51, 2%) and the Batak tribe as many as 42 students (45.2%). Media Information shows, respondents read 2-3 types of information as many as 44 students (47.3%), with less than 3 types of search as much information as 33 students (35.5%) and considered the best media to inform the treatment of less than 3 as many as 56 types of students (60.2%). Categories of knowledge respondents are in good category as many as 79 students (84.9%), the attitude of the respondents were in either category were 68 students (73.1%) and respondents' actions are in either category were 72 students (77.4%). From the results of the study suggested the clump students to better understand the health faculty of knowledge that has been gained in the lecture bench and apply it in everyday life.ABSTRACT Treatment search process is a process performed by a person in response to pathological reactions that occur within his body. The search process is made up of medical knowledge and attitude towards his condition. Knowledge and attitudes can be formed of a good education. Clumps student health faculty learn it so, it would be good to see how the image of student behavior in the process searching of  medical treatment. This type of research is a descriptive study with a survey method. The population in this study were all students of the Faculty of Medicine (FK), School of Public Health (FKM) and School of Nursing (FKep) University of North Sumatra regular program who active force from 2009 to 2012 with a sample size of 93 student. The samples came from 44 medical students, 35 public health students and 14 students of Nursing Faculty. Presentation of data using frequency distribution tables. The results showed that the characteristics of the respondents had been studying for 2 and 4 semesters as many as 28 students (30.1%), female sex as many as 59 students (63.4%), with the 19-20 year age group as many as 48 students (51, 2%) and the Batak tribe as many as 42 students (45.2%). Media Information shows, respondents read 2-3 types of information as many as 44 students (47.3%), with less than 3 types of search as much information as 33 students (35.5%) and considered the best media to inform the treatment of less than 3 as many as 56 types of students (60.2%). Categories of knowledge respondents are in good category as many as 79 students (84.9%), the attitude of the respondents were in either category were 68 students (73.1%) and respondents' actions are in either category were 72 students (77.4%). From the results of the study suggested the clump students to better understand the health faculty of knowledge that has been gained in the lecture bench and apply it in everyday life.